(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
India is one of thefastest growing economy of the world. But this growth is accompanied with the crisis in the field of energysupplies, environmental control, population increase, poverty and shortage offood and material. Resource limitation today demands their judicial use, whichotherwise threatens to its end. Energy is the key indicator of sustainabledevelopment. Most of the powergeneration in India is carried out by conventional energy sources, coal andmineral oil-based power plants which contribute heavily to greenhouse gasesemission. India is one of the countries which blessed with numerousrenewable energy resources via. Solar power, hydro power, wind power andbiomass energy. The demand for renewable energy resources is increasing as itfulfils both the objectives of improvement in environmental conditions andpoverty alleviation. Solar energy when considered on human scale is renewableand is environmentally acceptable, but its use is still in primitive stage inmany parts of the country mainly because of economic barriers. Likewise,biomass energy is being used in many forms all over the world, but the mostneeded eco-friendly forms are still in premature stage in most of the world. Research, development, production anddemonstration have been carried out enthusiastically in India to find afeasible solution to the perennial problem of power shortage for the past threedecades. India has obtained application of a variety of renewable energytechnologies for use in different sectors too. This paper attempts to study thepresent status, challenges and future prospects of renewable energy in India.